Celebrating Difference: Eid al Fitr, Social Cohesion, and Religious Moderation in Magelang, Indonesia - Gunawan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
In Indonesia, the celebration of Eid al Fitr in a plural and complex society is not only a religious ritual for Muslims, but can also serve as a social space that strengthens cohesion and tolerance across identities. This study aims to analyse how the celebration of Eid al Fitr in Magelang, Indonesia, fosters interreligious harmony while renewing social attachment across identities through perceptions, values, and religious practices in the midst of diversity. This research employs a qualitative approach with a case study design. Data were collected through observation of the sequence of Eid al Fitr celebrations, including takbiran, the Eid prayer, halalbihalal, and house to house visits, as well as in depth interviews with key informants who directly experienced the dynamics of Lebaran visits and interreligious relations. The data were analysed iteratively through repeated reading, thematic grouping, and interpretation using Émile Durkheim’s framework of social solidarity, particularly mechanical solidarity, organic solidarity, and collective effervescence. The findings show that Eid al Fitr in Desa Pepe functions not only as a spiritual obligation, but also as a social mechanism that strengthens cohesion through shared emotions, norms of respect, and repeated social exchange. The findings also reveal that interreligious harmony is sustained through institutionalised coexistence and the negotiation of boundaries that preserve peaceful relations without blurring the distinct religious identities of each group. This study contributes to the strengthening of the sociology of religion, particularly in understanding religious ritual as a social practice that shapes interaction, identity, and shared life in a plural society. Di Indonesia, perayaan Idul Fitri di masyarakat yang majemuk dan kompleks tidak hanya menjadi ritus keagamaan umat Islam, tetapi juga dapat menjadi ruang sosial yang memperkuat kohesi dan toleransi lintas identitas. Penelitian ini bertujuan menganalisis bagaimana perayaan Idul Fitri di Magelang, Indonesia, menumbuhkan harmoni antar umat beragama sekaligus memperbarui keterikatan sosial lintas identitas melalui persepsi, nilai, dan praktik keagamaan di tengah keberagaman. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi terhadap rangkaian perayaan Idul Fitri, meliputi takbiran, salat Id, halalbihalal, dan silaturahmi dari rumah ke rumah, serta wawancara mendalam dengan informan kunci yang mengalami langsung dinamika kunjungan Lebaran dan relasi lintas agama. Data dianalisis secara iteratif melalui pembacaan berulang, pengelompokan tema, dan interpretasi dengan kerangka solidaritas sosial Émile Durkheim, terutama solidaritas mekanik, solidaritas organik, dan collective effervescence. Hasil penelitian menunjukkan bahwa Idul Fitri di Magelang tidak hanya berfungsi sebagai kewajiban spiritual, tetapi juga sebagai mekanisme sosial yang memperkuat kohesi melalui emosi bersama, norma penghormatan, dan pertukaran sosial yang berulang. Temuan ini juga memperlihatkan bahwa harmoni lintas agama dipelihara melalui koeksistensi yang terlembaga dan negosiasi batas yang menjaga hubungan tetap rukun tanpa mengaburkan identitas keagamaan masing-masing. Penelitian ini berimplikasi pada penguatan kajian sosiologi agama, khususnya dalam memahami ritual keagamaan sebagai praktik sosial yang membentuk interaksi, identitas, dan kehidupan bersama dalam masyarakat plural.